Nanoformulations Downregulating METTL16 Combined with mRNA Tumor Vaccines Suppress Triple-Negative Breast Cancer and Prevent Metastasis - Wang R; Zhang Y; Du S; Li Y; Ren Y; Lin J (International Journal of Nanomedicine)
Runying Wang,1,* Yufeng Zhang,1,* Shubo Du,1 Yanhua Li,2 Yanying Ren,3 Jiaqi Lin1 1MOE Key Laboratory of Bio-Intelligent Manufacturing, School of Bioengineering, Dalian University of Technology, Dalian, Liaoning, 116024, People’s Republic of China; 2Department of International Medical Department, the Second Affiliated Hospital of Dalian Medical University, Dalian, Liaoning, 116021, People’s Republic of China; 3Hernia and Colorectal Surgery Department, the Second Affiliated Hospital of Dalian Medical University, Dalian, Liaoning, 116023, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jiaqi Lin, School of Bioengineering, Dalian University of Technology, Dalian, Liaoning, People’s Republic of China, 116024, Tel +86 13125472686, Email jqlin@dlut.edu.cn Yanying Ren, Hernia and Colorectal Surgery Department, the Second Affiliated Hospital of Dalian Medical University, Dalian, Liaoning, People’s Republic of China, 116023, Email renyanying@dmu.edu.cnPurpose: Triple-negative breast cancer (TNBC) poses a significant threat to women’s health due to its high malignancy and recurrence. Traditional treatments such as surgical resection, radiotherapy, and chemotherapy are no longer sufficient to meet clinical needs. Based on prior research that identified METTL16 as a potential target for TNBC, this study aimed to develop a nanoformulation to mitigate the malignancy of TNBC by silencing METTL16. The integration of this formulation with emerging mRNA tumor vaccines aimed to effectively inhibit the growth and metastasis of TNBC.Research Methods: Using microfluidic technology, efficient siRNA encapsulation in lipid nanoparticle (LNP) yielded LNP/siMETTL16 and selective organ-targeting LNP/siMETTL16 (SORT-LNP/siMETTL16). Initially, the antitumor properties of LNP/siMETTL16 were evaluated at the cellular level. Subsequently, the antitumor properties were explored in mouse subcutaneous TNBC models with LNP/siMETTL16 (intratumoral injection) and mRNA tumor vaccines (intramuscular injection). The combined inhibition of TNBC lung metastasis by SORT-LNP/siMETTL16 (intravenous injection) and mRNA vaccine (intramuscular injection) was also investigated.Results: Cellular experiments demonstrated the efficient silencing effect of LNP/siMETTL16, leading to inhibition of tumor cell activity. The combination of LNP/siMETTL16 and LNP/mMUC1 significantly suppressed subcutaneous tumor growth, achieving an inhibition rate of 66.0%. Furthermore, the combination of SORT-LNP/siMETTL16 and mRNA tumor vaccines markedly alleviated TNBC lung metastasis.Conclusion: This study provides evident support for the application and translation of METTL16 as a therapeutic target and offers a novel strategy for TNBC combined treatment in clinical settings.Keywords: triple-negative breast cancer, METTL16, gene silencing, mRNA tumor vaccine, combined therapy